Od-uczyć się tęsknoty za minionym - rozważania o współczesnej starości - Majewska-Kafarowska, Agnieszka (Edukacja Dorosłych, 2023)
This article is devoted to the reflections on the specific nature of old age derived from the author’s inspirations with the categories found in the works by Zygmunt Bauman, Tadeusz Sławek and Krzysztof Maliszewski. Those are reflections on the phenomenon of ageing which is anchored in the post-modern culture. The author suggests that old age should be perceived not only as a social and demographic phenomenon occurring on the socio-cultural, economic, political or historical ground, but also as personal experience, an individual project, time in life experienced as a period without coercion but with the right to live one’s own way, in one’s own rhythm and on one’s own.